2019
DOI: 10.20944/preprints201906.0216.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dietary Fiber and Gut Microbiota in Renal Diets

Abstract: Nutrition is crucial for the management of patients affected by chronic kidney disease to slow down disease progression and to correct symptoms. The mainstay of nutritional approach to renal patients is protein restriction coupled with adequate energy supply to prevent malnutrition. However, other aspects of renal diets, including fiber content, can be beneficial. This paper summarizes the latest literature on the relationship between the type of dietary fiber and prevention and management of CKD, with special… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The bulking effect of dietary fiber is important for colonic health and gut motility. Dietary fiber leads to uremic toxin excretion by increasing stool output ( 42 ), secondary to increased proteolytic activities by protein fermenting bacteria ( 43 ). A systemic review including 203 patients with CKD from seven reports showed that dietary fiber reduced p-cresyl sulfate, thereby protecting the intestinal epithelial barrier of patients with CKD ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The bulking effect of dietary fiber is important for colonic health and gut motility. Dietary fiber leads to uremic toxin excretion by increasing stool output ( 42 ), secondary to increased proteolytic activities by protein fermenting bacteria ( 43 ). A systemic review including 203 patients with CKD from seven reports showed that dietary fiber reduced p-cresyl sulfate, thereby protecting the intestinal epithelial barrier of patients with CKD ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it reduces the number of patients in the need of kidney replacement (Garneata et al, 2016). Thus, the nutritional approach to many renal diseases is protein restriction associated with adequate energy supply to prevent malnutrition (Camerotto et al, 2019).…”
Section: Proteinsmentioning
confidence: 99%
“…Fiber intake can be beneficial for chronic renal diseases, with activities towards gut microbiota (Camerotto et al, 2019). A study considered the dietary intake of carbohydrates, sugar, starch, cereal, vegetable, and fruit fiber, with the onset of chronic kidney disease.…”
Section: Fibersmentioning
confidence: 99%